(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
It is generally believed that study abroad is one of the most efficient and successful ways to acquire proficiency in a second language (L2), since learners find themselves in situations in which they can use the language on a daily basis and interact with native speakers. After a wealth of research on the L2 outcomes of Spanish immersion programs, many questions pertaining to the acquisition of patterns of language variation common to a particular community in an SA context remain unanswered. This article explores the extent to which a group of learners of Spanish acquire variable structures of language - specifically, the leísmo phenomenon- while participating in a five-month study-abroad immersion program in Valladolid (Spain). The results suggest that SA learners do in fact develop an awareness of non-standard forms of the target language, which are, to a certain degree, incorporated into their sociolinguistic competence. In sum, this study adds further knowledge about the development of L2 linguistic competence during a sojourn abroad, and fills a gap in the new strand of studies on the acquisition of dialectal variation.